Bile acid receptors and renal regulation of water homeostasis - Guo, Yanlin; Luo, Taotao; Xie, Guixiang; Zhang, Xiaoyan (Frontiers in Physiology, 2023)
The kidney is the key organ responsible for maintaining the body’s water and electrolyte homeostasis. About 99% of the primary urine filtered from the Bowman’s capsule is reabsorbed along various renal tubules every day, with only 1–2 L of urine excreted. Aquaporins (AQPs) play a vital role in water reabsorption in the kidney. Currently, a variety of molecules are found to be involved in the process of urine concentration by regulating the expression or activity of AQPs, such as antidiuretic hormone, renin-angiotensin-aldosterone system (RAAS), prostaglandin, and several nuclear receptors. As the main bile acid receptors, farnesoid X receptor (FXR) and membrane G protein-coupled bile acid receptor 1 (TGR5) play important roles in bile acid, glucose, lipid, and energy metabolism. In the kidney, FXR and TGR5 exhibit broad expression across all segments of renal tubules, and their activation holds significant therapeutic potential for numerous acute and chronic kidney diseases through alleviating renal lipid accumulation, inflammation, oxidative stress, and fibrosis. Emerging evidence has demonstrated that the genetic deletion of FXR or TGR5 exhibits increased basal urine output, suggesting that bile acid receptors play a critical role in urine concentration. Here, we briefly summarize the function of bile acid receptors in renal water reabsorption and urine concentration.